Maternal age at childbirth and the risk of attention-deficit/hyperactivity disorder and learning disability in offspring - Gao, Ling; Li, Songtao; Yue, Yulin; Long, Guangfeng (Frontiers in Public Health, 2023)
Background: Studies have shown that young maternal age at childbirth can increase the risk of attention-deficit/hyperactivity disorder (ADHD) in offspring, but a study of the U.S. population has not been reported. Moreover, there is no reported research on young and advanced maternal age at childbirth and whether it can contribute to the risk of learning disability (LD) in offspring. Methods: This study evaluated the association between young and advanced maternal age at childbirth and offspring risk of ADHD and LD in the U.S. population. Using data from 8,098 participants included in the National Health and Nutrition Examination Survey (NHANES) conducted in 1999–2004, we analyzed the association between maternal age at childbirth and ADHD and LD risk in offspring. Odds ratios (ORs) and 95% confidence intervals (CIs) for maternal age at childbirth in association with ADHD and LD risk in offspring were estimated using multivariate logistic regression models after adjustment for age, sex, race, body mass index (BMI), poverty income ratio, smoking status during pregnancy, and NHANES cycle. Restricted cubic spline (RCS) models were used to evaluate potential nonlinear relationships. Sensitivity analyses were performed to ensure the reliability of the results. Results: Among all participants, the offspring of subjects with a maternal age at childbirth of 18–24 years had an increased risk of ADHD (OR=1.34, 95% CI: 1.01, 1.79) and LD (OR=1.36, 95% CI: 1.06, 1.79) or either ADHD or LD (OR=1.48, 95% CI: 1.20, 1.81). Additionally, compared with subjects with a maternal age at childbirth of 25–29 years, subjects with a maternal age at childbirth of 35–39 years had lower odds of having offspring with ADHD (OR=0.60, 95% CI: 0.36, 1.00) and higher odds of having offspring with LD (OR=1.34, 95% CI: 1.01, 1.78). The relationship between maternal age at childbirth and LD risk presented a U-shaped curve. Conclusions: These results provide epidemiological evidence showing that young and advanced maternal age at childbirth are associated with ADHD and LD risk.